The Value of Programmable Shunt Valves for the Management of Subdural Collections in Patients with Hydrocephalus - Dimitrios Pachatouridis; George A. Alexiou; Evaggelos Mihos; George Fotakopoulos; Spyridon Voulgaris (The Scientific World Journal)
Background. The aim of the present study was to assess the value of electromagnetic programmable shunt valves for the treatment of subdural collections. Methods. Adult patients with hydrocephalus of various causes that were treated with programmable shunt valves during the last ten years were retrospectively studied. In 127 patients, 139 electromagnetic programmable shunt valves were implanted. Results. A nontraumatic subdural fluid collection was detected in 12 patients. The treatment of these patients consisted of reprogramming of the valve’s opening pressure. In 5 patients small subdural hematomas were detected; 4 of these patients were treated by raising the opening pressure alone and one patient required surgical drainage and change of the pressure setting. Traumatic chronic subdural hematomas were detected in 6 patients. These patients were treated by surgical drainage and readjustment of the valve’s opening pressure. Conclusion. The ability to treat a shunt-related complication, such as a subdural fluid collection, by reprogramming the valve’s opening pressure to a higher setting is an advantage over nonprogrammable valves, and it enables the opening pressure to be slowly lowered once the fluid collection is reabsorbed. Based on our results, we believe that programmable shunt valves should be preferred.